A synthesis of current literature and knowledge about the ecology of the puma (Puma concolor Linnaeus) - López González, Carlos A.; González Romero, Alberto (Instituto de Ecología, A.C., 1998)
A literatura survey was carried out in severa! universities and databases from the United States and México, and discussions were held with many carnivore biologists to summarize the current and most relevant knowledge on the ecology of the puma (Puma concolor). The main objective was to update our ecological knowledge from the last literature reviews published in 1987. Comments are made on sample sizes, different methodologies, and how these make comparisons hard to achieve between areas or studies, and suggest where research should be directed in the future based upon gaps found in this literature survey.